PENGARUH LINGKUNGAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT PERKEBUNAN NUSANTARA V PEKANBARU (KASUS PADA KARYAWAN BAGIAN SDM) - Ummi Kaltsum; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to determine the effect of work environment and organization commitment to employees performance of human resources at PT Perkebunan Nusantara V Pekanbaru partially and simultaneously. Dimensions are used in work environment consists of work atmosphere, relationships with colleagues, and availability of working facilities. Dimensions variable organization commitment consists of affective commitment, continuous commitment, and normative commitment. And dimensions for the independent variables (employees performance) consists of labor quantity, labor quality, reliability, presence, and ability to cooperate. The method used is descriptive analysis method, and multiple linear analysis method that produces output t test, F test, and test of the determinant (R²). Processing data using programe SPSS 20.The results showed that the partial work environment does not significantly effect on employees performance of human resources at PT Perkebunan Nusantara V Pekanbaru, as shown by the significant value greater than 0,05. Partial variable organization commitment significantly influence employee employees performance of human resources at PT Perkebunan Nusantara V Pekanbaru,. And simultaneous work environment and organization commitment a significant effect on employees performance. Based on research obtained the degree of correlation of 0.832 which indicates that the level of relationship between the independent variable on the dependent variable has a strong relationship and R² values obtained at 0.692 or 69,2%. This means that employees performance of human resources at PT Perkebunan Nusantara V Pekanbaru influenced by work environment and organization commitment employees amounted to 69,2%.Keywords: Work Environment, Organization Commitment, Employees Performance